Perceived Pain during Cataract Surgery with Topical Anesthesia: A Comparison between First-Eye and Second-Eye Surgery - Lin Jiang; Keke Zhang; Wenwen He; Xiangjia Zhu; Peng Zhou; Yi Lu (Journal of Ophthalmology)
Purpose. To compare pain scores between first-eye and second-eye cataract surgery and to determine the affecting factors. Methods. 106 first-eye and 53 second-eye cataract surgery patients (mean age: 67 ± 13 and 69 ± 10 years, resp.) were enrolled. The patients completed simplified State-Trait Anxiety Inventory and visual analog scale (VAS) for anxiety questionnaires before surgery, and VAS for pain and Wong-Baker Faces Pain Rating Scale questionnaires after surgery. Blood pressure (BP) and heart rate (HR) were recorded perioperatively. Results. A greater proportion of patients who underwent second-eye surgery reported intraoperative pain compared with first-eye surgery patients (85% versus 35%, P<0.001). The pain scores were higher in second-eye surgery, while the VAS anxiety score was lower in second-eye surgery. Moreover, 31 patients reported greater pain during second-eye surgery than their first one, with higher pain scores than other 22 patients (P=0.032 and 0.003, resp.). The VAS pain score of these 31 patients was positively correlated with the differences between the intraoperative and postoperative diastolic BP, mean arterial pressure, and HR. Conclusions. Cataract patients were likely to have more pain during second-eye surgery, which may be related to lower preoperative anxiety. Monitoring perioperative BP and HR may help to identify patients with intraoperative pain.